2018
DOI: 10.1155/2018/1096056
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Dynamic Responses and Head Injuries of Standing Subway Passengers during Collisions

Abstract: With the development of the subway and the pressing demand of environmentally friendly transportation, more and more people travel by subway. In recent decades, the issues about passenger passive safety on the train have received extensive attention. In this research, the head injury of a standing passenger in the subway is investigated. Three MADYMO models of the different standing passenger postures, defined as baseline scenarios, are numerically set up. HIC15 values of passengers with different postures are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…24,25 In the 1950s, research on roadway traffic safety led to the development of biomechanics of head impact and spawned a significant criterion to assess head injury criterion (HIC), which had been widely addressed in rail vehicle and automotive impact accidents. 26 Although passive train safety and occupant safety have been widely studied, few studies involved occupant safety due to train overturn accidents. According to the limited study on train overturn accidents, it found the patterns of injuries from train overturn accidents are different from that of train collision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 In the 1950s, research on roadway traffic safety led to the development of biomechanics of head impact and spawned a significant criterion to assess head injury criterion (HIC), which had been widely addressed in rail vehicle and automotive impact accidents. 26 Although passive train safety and occupant safety have been widely studied, few studies involved occupant safety due to train overturn accidents. According to the limited study on train overturn accidents, it found the patterns of injuries from train overturn accidents are different from that of train collision.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 In the 1950s, research on roadway traffic safety led to the development of biomechanics of head impact and spawned a significant criterion to assess head injury criterion (HIC), which had been widely addressed in rail vehicle and automotive impact accidents. 26…”
Section: Introductionmentioning
confidence: 99%